PENGARUH KEPEMIMPINAN DAN MOTIVASI TERHADAP KOMITMEN ORGANISASIONAL DENGAN MEDIASI KEPUASAN KERJA GURU - Ariwigunadi, Nugroho (Students Journal of Economic and Management, 2012)
This study aimed to analyze the influence of the Principal Transformational Leadership on Job Satisfaction and Motivation high schools in the District of Batang with Organizational Commitment as mediation variables. In this study population of 102 people, while the sample taken as many as 81 people as respondents with a purposive sampling method. With all of the criteria of civil servants in SMA N 1 and 2 Trunk. Measurements using a Likert scale of 7 (seven) alternative answers. Test instruments used are validity and reliability. While the test model used is the coefficient of determination and F test (goodnes of Fit). Hypothesis testing used in this study used regression analysis. Based on the results of the study can be summarized as follows: (i) the principals leadership significantly influence Commitment Job Satisfaction, (ii) Motivation significant effect on Job Satisfaction (iii) the principals leadership influence on Job Satisfaction, (iv) Motivation no significant effect on Commitment organizational, (v) Job Satisfaction no significant effect on Organizational Commitment, (vi) Job Satisfaction does not mediate the effect of variable principals leadership on Organizational Commitment, and (vii) Job Satisfaction Motivation does not mediate the effect of variables on Organizational Commitment. Keywords: Principal Leadership, Motivation, Job Satisfaction, and Organizational Commitment.